A history of the World Tourism Organization - Shackleford, Peter (Emerald Publishing Limited, 2020)
Tourism and travel have been with us since time immemorial. However, with the onset of the industrial age and the use of railways, ships, motorcars, and aeroplanes, travelling possibilitiesfor both business and pleasure, domestic and internationalwere transformed. The annals of the United Nations World Tourism Organization (UNWTO) provide us with unmatched insights into this fascinating story, yet these archives have never been exhaustively exploited. The History of the World Tourism Organization takes us on a unique journey to explain how tourism has burgeoned between the early twentieth century and now. Drawing on the UNWTO's regularly published tourism statistics, this book provides comprehensive discussions of the consequences of an unhindered flow of tourists; the consequent protection of natural assets; the safeguarding of tourism resources; how frontier formalities affect this sector; how tourism impacts on world trade; and the promotion of tourism to countries in economic decline. Collectively, these investigations offer an impartial understanding of modern tourism and its effects. This definitive overview of this major intergovernmental organization is a must-read for students and scholars of tourism and hospitality, and it is of interest to anyone concerned with the past, present, and future of this ever-evolving and fundamentally human practice.
Includes indexes.
Keywords: World Tourism Organization -- History.; Tourism -- History.; Travel -- General.; Tourism industry.; elektronické knihy; electronic books